Modern approaches to the assessment of respiratory failure in children (Herald of the National Children's Medical Center, 2024)
Abstract: This article is devoted to determining the role of laboratory kidney parameters in the integral assessment of the condition and predicting the outcomes of children with critical conditions at the prehospital stage of emergency medical care.Materials and methods of research: The observation group consisted of children aged 2 months to 14 years who were admitted to the admission and diagnostic department of the clinic of the Tashkent Pediatric Medical Institute and the children's building of the Republican Scientific Center for Emergency Medical Care with signs of respiratory failure.Results of the study: Hyperthermia, convulsive syndrome, respiratory failure of various degrees, and surgical pathology in 15 children were the reason for the children's referral to the emergency diagnostic department in 73 cases. As a result of the analysis of the data obtained, a structural approach to the assessment of respiratory disorders was determined, which allows timely assessment of the condition of the incoming child and determine further actions, as well as informative indicators of respiratory dysfunction in young children and older children.Conclusion: A structural approach to the assessment of respiratory disorders makes it possible to timely assess the condition of the incoming child and determine further actions. Informative indicators of respiratory dysfunction in young children are respiratory rate and oxygen saturation, in older children the indicator of peak exhalation rate.
Keywords: respiratory function; assessment scale; threatometry; assessment systems; structural approach; emergency conditions; respiratory disorders